Are ERP and Organization Capability can be Enablers of Green Supply Chain Management ? A viewpoint from employees’ perception - Hasnawati Zainal; Milan Oresky (Indonesian Management and Accounting Research, 2018)
The objectives of this research are to see the influence of Enterprise Resource Planning (ERP) implementation and organizational capability toward Green Supply Chain Management (GSCM) practices. GSCM practices are seen through green purchasing, cooperation with customers, and investment recovery practices. ERP implementation is measured using integration, configuration, and adaptation of the organization information system. Meanwhile, organization capabilities are measured by information access, product innovation, and flexibilities.This research uses a convenience sampling technique by distributing questioner 60 respondents. They are employees who work in different types of companies. The results showed that ERP implementation influences the practice of cooperation with customers, while ERP practices do not influence green purchasing and investment recovery practices.  Organizational capabilities also do not influence the practice of GSCM.